Organization of TNIK in dendritic spines. Issue 13 (1st July 2015) - Burette, Alain C.; Phend, Kristen D.; Burette, Susan; Lin, Qingcong; Liang, Musen; Foltz, Gretchen; Taylor, Noël; Wang, Qi; Brandon, Nicholas J.; Bates, Brian; Ehlers, Michael D.; Weinberg, Richard J.
ABSTRACT Tumor necrosis factor receptor‐associated factor 2 (TRAF2)‐ and noncatalytic region of tyrosine kinase (NCK)‐interacting kinase (TNIK) has been identified as an interactor in the psychiatric risk factor, Disrupted in Schizophrenia 1 (DISC1). As a step toward deciphering its function in the brain, we performed high‐resolution light and electron microscopic immunocytochemistry. We demonstrate here that TNIK is expressed in neurons throughout the adult mouse brain. In striatum and cerebral cortex, TNIK concentrates in dendritic spines, especially in the vicinity of the lateral edge of the synapse. Thus, TNIK is highly enriched at a microdomain critical for glutamatergic signaling. J. Comp. Neurol. 523:1913–1924, 2015 © 2015 Wiley Periodicals, Inc.